An Economic Analysis of Bank Regulatory Reform: The Financial Institutions Safety and Consumer Choice Act of 1991 - Michael Klausner (Washington University Law Quarterly, 1991)
This Article analyzes the interaction between the bank regulatory system and the market for financial services and examines the ways in which bank regulation affected profitability and risk-taking both before and after 1980. The Article focuses on the range of business strategies available to banks during each period and the incentives operating on bank shareholders and managers in selecting from available strategies. The Article suggests that although banks have always been subject to restrictions in the services they may provide, before 1980 those restrictions did not prevent banks from adopting profitable, low-risk business strategies. Indeed, the bank regulatory system induced banks to adopt such strategies. As a result of changes in financial services markets that began in the mid-1970s, however, the profitability of legally permissible low-risk strategies declined for many banks. The deposit insurance system's implicit subsidy of risk-taking consequently became more attractive to bank shareholders and managers than it had been in past. The Article then suggests the type of regulatory reform that is necessary in order to allow banks to operate effectively in the modem market for financial services. Finally, the Article discusses the ways in which FISCCA would respond to the need for reform.
Keywords: Banking industry; Consumer protection